(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present study investigated the relationships between locus of control, automatic self-thoughts, self-esteem, and academic anxiety among high school students (50 boys, 50 girls) in Delhi, India. Using standardized measures Rotter’s Internal-External Locus of Control Scale, Automatic Thoughts Questionnaire, Rosenberg’s Self-Esteem Scale, and Academic Anxiety Scale for Children the study employed Pearson correlation analyses to test hypotheses positing no significant relationships between these variables and academic anxiety. Results revealed significant correlations: a negative correlation between locus of control and academic anxiety (r = -0.215, p < .05), a strong negative correlation between self-esteem and academic anxiety (r = -0.816, p < .01), and a strong positive correlation between automatic thoughts and academic anxiety (r = 0.858, p < .01). These findings suggest that students with external locus of control and high self-esteem experience lower academic anxiety, while those with frequent negative automatic thoughts experience higher academic anxiety. Implications for educational counseling and future research are discussed.